2016
DOI: 10.1186/s40035-016-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Beclin-1- mediated autophagy may be involved in the elderly cognitive and affective disorders in streptozotocin-induced diabetic mice

Abstract: BackgroundDiabetes is the most common metabolic disease with many chronic complications, and cognitive disorders are one of the common complications in patients with diabetes. Previous studies have showed that autophagy played important roles in the progression of metabolic syndrome, diabetes and other diseases. So we investigated whether aged diabetic mice are prone to be associated with the cognitive and affective disorders and whether Beclin-1-mediated autophagy might be involved in thepahological process.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…Autophagy is a highly conserved metabolic process that is present in eukaryotic cells. Autophagy leads to the degradation of cytoplasmic components in lysosomes and has recently attracted considerable attention due to its association with DM-induced cognitive deficits (30). Observed autophagy impairments in the hippocampus of GK rats may result in a reduction in hippocampal cell viability and dendritic spine density (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a highly conserved metabolic process that is present in eukaryotic cells. Autophagy leads to the degradation of cytoplasmic components in lysosomes and has recently attracted considerable attention due to its association with DM-induced cognitive deficits (30). Observed autophagy impairments in the hippocampus of GK rats may result in a reduction in hippocampal cell viability and dendritic spine density (31).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy serves an important role in maintaining normal tissue and cellular homeostasis (10). A previous study revealed the crucial role of autophagy in DM, in which autophagy functions to ameliorate or exacerbate DM-induced cognitive dysfunction (9,11). Therefore, regulation of autophagy in the hippocampus may be considered an essential method to ameliorate neuronal damage.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired autophagy triggers inflammasome activation because antiapoptotic Bcl‐2 family members interact with BECN1, and thus, nuclear factor kabba B (NF‐κB)‐driven antiapoptotic Bcl‐2 proteins repress the BECN1‐dependent autophagy. STZ diabetic mice showed significantly decreasing abilities in spatial memory and conditioned fear memory (all P < 0.05) and the increasing tendency of depression ( P < 0.05) . The affected mice had cerebral microvascular disease involving hippocampal atrophy, ventricular dilatation, and leukoaraiosis, and decreased glucose metabolism in the amygdala and hippocampus ( P < 0.05).…”
Section: Relationship Of Beclin 1 To Appmentioning
confidence: 96%
“…In more relevance to AD neuropathology, beclin-1 is downregulated in this disease; however, LC3-II can still form without a phagophore on ectopic membrane fragments [21,25] . Beclin-1, an adaptor protein via its partner proteins, can either stimulate or suppress the onset of autophagy [27] . In this study, we observed that beclin-1 levels were elevated in AD patient's platelet.…”
Section: Discussionmentioning
confidence: 99%